Aspirations to study medicine, perceptions of a good doctor, and their influence on specialty choice among medical students - Quang Thanh Nguyen; Thuong Thi Ha Luong; Hoang Viet Nguyen; Minh Quang Ngo; Son Hoang Nguyen; Ngoc Luong Khanh Nguyen (PLoS ONE, 2025)
Background Specialty decision-making among medical students reflects a complex interplay of motivations, evolving perceptions, and experiences during medical training. This study explores how students’ initial motivations, views on what makes a good doctor, and academic progression influence their specialty preferences. Methods A mixed-methods study was conducted at VinUniversity, a not-for-profit medical school in Vietnam. Quantitative surveys were completed by 155 students across Years 1–4 (79.5% response rate), and 27 students participated in in-depth interviews. Quantitative data were analyzed using Wilcoxon rank-sum and Kruskal-Wallis tests. Qualitative responses underwent thematic analysis to explore identity formation and specialty choice. Results Altruism was the most cited factor influencing specialty choice, with “desire to help people” rated highest (4.08 ± 1.14). Students’ perceptions of essential doctor qualities evolved over time. Younger students valued creativity (p = 0.035) and innovation (p = 0.022) more than seniors, reflecting a shift toward practicality in later years. Specialty preferences aligned with professional values: students favoring surgery rated work ethic (p = 0.029), collaboration (p = 0.006), and adaptability (p = 0.044) higher than those preferring internal medicine. Students inclined toward pediatrics or psychiatry prioritized empathy and communication, while those choosing surgery emphasized technical skill and decisiveness. Female students rated prestige as more influential than male students (p = 0.049). Qualitative data revealed that clinical exposure and self-reflection helped students refine their specialty choices by aligning personal traits with perceived specialty demands. Conclusion Medical students’ specialty preferences are shaped by their initial motivations, developing perceptions of good doctor qualities, and experiences throughout training. These findings underscore the need for medical curricula and mentorship to address the evolving identity and values of students, supporting more informed and aligned specialty choices.